The Urgence Of Islamic Philosophy For Education In Elementary School - Siti Nurhalisa; Anika Musayadah; Naila Ulfatusy Syarifah; Adila Puspitasari; Nasikhin Nasikhin; Mahfud Junaedi (UPT Pusat Studi Aswaja UNISNU Jepara, 2022)
AbstractThe growing opinion that philosophy is a teaching that is prohibited in Islam often has a negative impact on education, especially for basic education. This study aims to determine the role of Islamic educational philosophyfor Islamic basic education. This study uses the literature study method to find information related to the theme of Islamic philosophy as a science at the basic education level. From the results of the analysis that has been carried out, research data shows that the importance of Islamic philosophy for basic education in three roles is the reason; First, the philosophy of Islamic education plays a role in compiling thinking activities to find the concept of basic education in overcoming various problems of Islamic education through the study of the Qur'an and Hadith. Second, the philosophy of Islamic education leads basic education teachers to develop critical thinking on material objects and formal objects. Material objects include all existing realities (forms), while formal objects are closely related to human nature from the point of view of basic Islamic education. This role is carried out through the method of selection, search, discussion, and a comprehensive approach to the study of Islamic basic education philosophy. This research contributes to the development of education so that it is not anti-philosophical.Keywords: Philosophy, Islam, Elementary Schools.AbstrakOpini yang berkembang bahwa filsafat merupakan ajaran yang dilarang dalam Islam acapkali memberikan dampak buruk terhadap pendidikan, khusunya jenjang pendidikan dasar. Kajian ini bertujuan untuk mengetahui peranan filsafat pendidikan Islam bagi pendidikan dasar Islam. Penelitian ini menggunakan metode studi pustaka untuk menggali informasi terkait tema filsafat islam sebagai ilmu pada jenjang pendidikan dasar. Dari hasil analisis yang telah dilakukan diperoleh data penelitian yang menunjukkan bahwapentingnya filsafat Islam bagi pendidikan dasar didasarkan pada tiga peran yang menjadi alasan; pertama, filsafat pendidikan islam berperan dalam menyusun aktivias berpikir untuk menemukan konsep pendidikan dasar dalam mengatasi berbagai problem pendidikan Islam melalui kajian al-Qur'an dan Hadist. Kedua, filsafat pendidikan islam menggiring guru pendidikan dasar untuk menyusun pemikiran kritis atas objek materiil dan objek formal. Objek materi meliputi segala realitas yang ada (wujud), sedangkan objek formal berhubungan erat dengan hakikat manusia dari sudut pandang pendidikan dasar Islam. Peranan ini terlaksana melalui metode pemilihan, pencarian, pembahasan, dan pendekatan studi filsafat pendidikan dasar Islam yang dilakukan secara komprehensif.Penelitian ini memberikan kontribusi bagi perkembangan pendidikan agar tidak bersifat anti-filsafat.Kata Kunci: Filsafat, Islam, Pendidikan Dasar